Clinical Magnetic Resonance Imaging / Edited by Robert R. Edelman, John Hesselink, Michael Zlatkin, John V. Cruces III ; Contributors Essam Abou-Bieh, David Alsop y otros doscientos cuarenta y cinco más... - Edelman, Robert R.; Hesselin, John R.; Zlatkin, Michael B.; Crues, III, John V.; Abou-Bieh, Essam; Alsop, David (Philadelphia : Saunders Elservier, 2006)
Presenta cada capítulos individuales son muy accesible y fácil de leer. Incluyen tablas de contenido, índices, y, con el acceso en línea, buscar, indexar y herramientas de referencia cruzada. El tema es excelente, las imágenes son excepcionales, apropiada y extensa.
Table of Contents VOLUME 1 I. PHYSICS, INSTRUMENTATION, AND ADVANCED TECHNIQUES 1. History 2. Basic Principles 3. Practical Considerations and Image Optimization 4. Instrumentation: Magnet, Gradients, and Coils 5. Pulse Sequence Design y otros más.. II. HEART 27. Magnetic Resonance Angiography: Basic Principles 28. Basic Principles and Clinical Applications of Flow Quantification 29. Principles and Optimization of Contrast-Enhanced Three-Dimensional Magnetic Resonance Angiography 30. Magnetic Resonance Angiography of the Body y otros más... VOLUME 2 III. BRAIN 39. Brain: Indications, Technique, and Atlas 40. Adult Brain Tumors 41. Brainstem, Cranial Nerves and Cerebellum 42. Pituitary Gland and Parasellar Region 43. Perfusion and MRS for Brain Tumor Diagnosis y otros más... V. SPINE 68. Spine Atlas 69. Spinal Cord and Intradural Disease 70. Degenerative Disease 71. Positional and Kinetic Spin Imaging 72. Post-operative Spine y otros más... VOLUME 3 VI. BODY 76. Chest, Including Lung Function 77. Breast Cancer 78. Breast Implants 79. MR Cholangiopancreatography 80. Gallbladder y otros más...
Volumen 1: Partes de Physics, instrumentation, and advanced techniques, heartand vascular system, paginas 1-1070 Volumen 2 : Partes de Brain, head and neck, spine, paginas 1071-2396 Volumen 3: partes de Boyd, musculoskeltal system, páginas 2397-3072
Incluye bibliografía e índice
Keywords: RESONANCIA MAGNETICA EN IMAGENES; DIAGNOSTICO POR IMAGENES; MAGNETIC RESONANCE IMAGING